2022
DOI: 10.1038/s41467-022-35435-7
|View full text |Cite
|
Sign up to set email alerts
|

An ionic vinylene-linked three-dimensional covalent organic framework for selective and efficient trapping of ReO4− or 99TcO4−

Abstract: The synthesis of ionic olefin linked three-dimensional covalent organic frameworks (3D COFs) is greatly challenging given the hardness of the formation of stable carbon-carbon double bonds (–C = C–). Herein, we report a general strategy for designing porous positively charged sp2 carbon-linked 3D COFs through the Aldol condensation promoted by quaternization. The obtained 3D COFs, namely TFPM-PZI and TAPM-PZI, showed impressive chemical stability. Furthermore, the positively charged frameworks with regular por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 57 publications
0
20
0
1
Order By: Relevance
“…This approach offers easy operation and high efficiency. Commonly used ion exchange materials include resins, , molecular compounds, silica, metal borates, , layered double hydroxide (LDH), , metal–organic frameworks (MOFs), ionic polymers, cationic covalent organic nanosheets (iCONs), and covalent organic frameworks (COFs), among others . Resins, molecular compounds, and LDH-based adsorbents all have limitations due to their relatively low 99 TcO 4 – adsorption capacity and poor selectivity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach offers easy operation and high efficiency. Commonly used ion exchange materials include resins, , molecular compounds, silica, metal borates, , layered double hydroxide (LDH), , metal–organic frameworks (MOFs), ionic polymers, cationic covalent organic nanosheets (iCONs), and covalent organic frameworks (COFs), among others . Resins, molecular compounds, and LDH-based adsorbents all have limitations due to their relatively low 99 TcO 4 – adsorption capacity and poor selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Resins, molecular compounds, and LDH-based adsorbents all have limitations due to their relatively low 99 TcO 4 – adsorption capacity and poor selectivity. Recently, MOFs and COFs have demonstrated excellent 99 TcO 4 – capture abilities, offering the advantages of a high uptake capacity, fast adsorption kinetics, and good selectivity. ,,, ,, Although MOFs and COFs display fast kinetics and high capacity under mild conditions, they are generally unsuitable for 99 TcO 4 – adsorption under strongly acidic, high ionic strength, or alkaline solutions due to instability issues (i.e., under conditions most relevant to the treatment of nuclear waste streams). , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Covalent organic frameworks (COFs) are emerging crystalline porous materials with network structures and preset skeletons, which are composed of lightweight organic building units through covalent bonds. Due to their high thermal and chemical stability, large specific surface areas, low skeleton density, and controllable structures, COFs have been applied in various fields such as catalysis technology, , gas separation and storage, , photoelectric materials, , ion extraction, , and antibacterial therapy. , To strengthen the generation of ROS in the COF-mediated photocatalytic process, some postsynthetic strategies such as the backbone modification, , functional group interconversion, , and metal deposition have been proposed. Loading metal nanoparticles or nanoclusters is considered to be an effective strategy to improve the photocatalytic properties of COFs in the midst of aforementioned strategies. , For instance, Zhang et al reported that the COFs loaded with Pt nanoparticles showed excellent catalytic activities in the reduction of nitrophenol and the Suzuki–Miyaura coupling reaction .…”
Section: Introductionmentioning
confidence: 99%
“…13,14 To date, only a few types of monomers have been explored for the construction of vinylene-linked COFs. 8–10,14–21 In addition, the synthesis of these monomers usually requires a complicated process and the utilization of toxic reagents (for instance, NaCN and CuCN) with high cost. 15 Therefore, it is urgently needed to develop monomers with low cost to construct vinylene-linked COFs.…”
mentioning
confidence: 99%